INTER-UNIVERSITY ACCELERATOR CENTRE, NEW DELHI (IUACD) RADIOCARBON DATE LIST I. Issue 5 (20th October 2020) - Sharma, Rajveer; Kumar, Pankaj; Ojha, Sunil; Gargari, Satinath; Chopra, Sundeep
ABSTRACT: A new facility for radiocarbon dating by accelerator mass spectrometry (AMS) was established in early 2015 at the Inter-University Accelerator Centre in New Delhi, India. The facility uses a 500 kV National Electrostatic Corporation (NEC) Pelletron accelerator for AMS measurements on graphite produced using the automated graphitization equipment (AGE) interfaced with an elemental analyzer and the carbonate handling system (CHS). A precision of better than 1‰ in the ratio of 14 C/ 12 C for the modern carbon sample and the background level of 1 × 10 –15 from dead carbon sample has been achieved. This is the first dedicated accelerator of India only for AMS activities. This AMS system has the capabilities to perform 10 Be and 26 Al measurements as well.